An evaluation of discharge documentation for people with dementia discharged home from hospital – A cross-sectional pilot study. (July 2019) - Kable, Ashley; Pond, Dimity; Hullick, Carolyn; Chenoweth, Lynnette; Duggan, Anne; Attia, John; Oldmeadow, Christopher
This study evaluated discharge documentation for people with dementia who were discharged home, against expected discharge criteria and determined relationships between compliance scores and outcomes. This cross-sectional study audited discharge documentation and conducted a post discharge survey of carers. There were 73 eligible discharges and clinically significant documentation deficits for people with dementia included: risk assessments of confusion (48%), falls and pressure injury (56%); provision of medication dose-decision aids (53%), provision of contact information for patient support groups (6%) and advance care planning (9%). There was no significant relationship between compliance scores and outcomes. Carer strain was reported to be high for many carers. People with dementia and their carers are more vulnerable and at higher risk of poor outcomes after discharge. There are opportunities for improved provision of medications and risk assessment for people with dementia, provision of information for patient support groups and advanced care planning.